Wearable Bifocal Contact Lens for Continual Glucose Monitoring Integrated with Smartphone Readers. Issue 51 (3rd October 2021) - Elsherif, Mohamed; Alam, Fahad; Salih, Ahmed E.; AlQattan, Bader; Yetisen, Ali K.; Butt, Haider
Abstract: Commercial implantable continuous glucose monitoring devices are invasive and discomfort. Here, a minimally‐invasive glucose detection system is developed to provide quantitative glucose measurements continually based on bifocal contact lenses. A glucose‐sensitive phenylboronic acid derivative is immobilized in a hydrogel matrix and the surface of the hydrogel is imprinted with a Fresnel lens. The glucose‐responsive hydrogel is attached to a commercial soft contact lens to be transformed into a bifocal contact lens. The contact lens showed bifocal lengths; far‐field focal length originated from the contact lens' curvature, and near‐field focal length resulting from the Fresnel lens. When tear glucose increased, the refractive index and groove depth of the Fresnel lens changed, shifting the near‐field focal length and the light focusing efficiency. The recorded optical signals are detected at an identical distance far from the contact lens change. The bifocal contact lens allowed for detecting the tear glucose concentration within the physiological range of healthy individuals and diabetics (0.0–3.3 mm ). The contact lens rapidly responded to glucose concentration changes and reached 90% of equilibrium within 40 min. The bifocal contact lens is a wearable diagnostic platform for continual biomarker detection at point‐of‐care settings. Abstract : A bifocal contact lens is demonstrated for glucose sensing under physiological conditions. The Fresnel lens imprinted on the glucose‐responsive hydrogel creates an additional focal length for the spherical monovision contact lens. Focusing efficiency and focal length of the Fresnel lens are altered by changing glucose concentrations in tears. Consequently, the reflected optical power can be used for glucose measurements.